1984
DOI: 10.3109/00365518409083604
|View full text |Cite
|
Sign up to set email alerts
|

A method for the determination of the total number of3H-ouabain binding sites in biopsies of human skeletal muscle

Abstract: A new method based on vanadate facilitated binding of 3H-ouabain has been applied for the quantitative determination of the number of 3H-ouabain binding sites (Na-K-pumps) in needle biopsies of human skeletal muscle. Samples of the vastus lateralis muscle weighing 2-8 mg showed specific and saturable binding of 3H-ouabain with an apparent KD of 1.9 X 10(-8) mol/l. In 20 healthy human subjects in the age range 25-80 years, the number of 3H-ouabain binding sites was 278 +/- 15 pmol/g wet weight with no relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 25 publications
7
94
0
Order By: Relevance
“…This conclusion should be drawn with some caution since possible variations in the techniques used by dierent laboratories have not been examined. However, since all studies have used the approach of Nùrgaard et al (1984) and Kjeldsen et al (1986) for optimal binding of 3 H-ouabain, these variations may probably be quite small.…”
Section: Eect Of Training On the Na-k Pump Concentrationmentioning
confidence: 95%
See 1 more Smart Citation
“…This conclusion should be drawn with some caution since possible variations in the techniques used by dierent laboratories have not been examined. However, since all studies have used the approach of Nùrgaard et al (1984) and Kjeldsen et al (1986) for optimal binding of 3 H-ouabain, these variations may probably be quite small.…”
Section: Eect Of Training On the Na-k Pump Concentrationmentioning
confidence: 95%
“…3.6.1.37) in biopsies of 3±10 mg was determined as described elsewhere (Evertsen et al 1997). These authors used the method described by Nùrgaard et al (1983Nùrgaard et al ( , 1984 and Kjeldsen (1986) but used N-2-hydroxyethylpiperazine-N 0 -2-ethanesulphonic acid (HEPES) as buer rather than TRIS in agreement with the recommendations of Good et al (1966). Separate control experiments showed that incubation in HEPES gave as high ouabain binding as in TRIS but that the variability was reduced (not shown).…”
Section: Biopsy Sampling and Enzyme Analysismentioning
confidence: 99%
“…The content of Na ϩ -K ϩ pumps in muscle biopsy samples was determined using the assay developed by Nørgaard et al (38) and employed previously in our laboratory (10). With the use of this procedure, two samples from each biopsy, weighing between 2 and 8 mg, are prewashed twice for 10-min periods in a Tris-sucrose buffer (10 mM Tris ⅐ HCl, 3 mM MgSO4, 1 mM Tris-vanadate, and 250 mM sucrose) containing sodium metavanadate (NaVO3) at 0°C.…”
Section: Subjectsmentioning
confidence: 99%
“…This procedure might induce several sources of error, such as loss of tissue constituents during incubation, tissue swelling during incubation with ouabain, and unequal blotting and evaporation before and during weighing. However, experiments have shown that the procedure does not change the net wet weight of the samples ( 18). Determination of sample wet weight 1 or 2 minutes after blotting causes an overestimation of the ('H)ouabain binding site concentration by factors of 1.03 or 1.05, respectively.…”
Section: Clinical Observationsmentioning
confidence: 99%